The Relationship Between The Implementation of Triage and The Incidence of Overcrowded in the Emergency Department of Adi Husada Kapasari Hospital, Surabaya, Indonesia - Suroso, Heri; Paraswati, Mareta Deka; Apriliana, Bela; Fauziyah, Febrike Inggit; Hartanto, Mey Vina Wirianti (Universitas Airlangga, 2023)
Introduction: The emergency department (ED) is at the forefront of hospital healthcare and is expected to provide timely and effective care. The imbalance of the need for emergency care and the availability of hospitals to provide health services has an impact on the occurrence of overcrowded situations. This study aims to determine the relationship between the implementation of triage and the incidence of overcrowded in the ED of Adi Husada Kapasari Hospital. Methods: This study uses a correlation study design with a cross sectional approach. The population in the study were all nurses in the ED of Adi Husada Kapasari Hospital, Surabaya, Indonesia, and 14 nurses were involved as respondents through a total sampling technique. The independent variable is the implementation of triage, the dependent variable is the incidence of overcrowded. Data collection using a questionnaire sheet to measure the implementation of triage, and the NEDOCS scale (National Emergency Department Overcrowding Scale) to measure the incidence of overcrowded. Data was analyzed using Spearman rank correlation test with α = 0.05. Results: The results showed that more than half respondents (64.3%) practice triage in moderate level, and the overcrowded assessment showed all respondents (100%) in the level 1, which means it was in category not busy. Spearman rank correlation test showed that there was no relationship between the implementation of triage and the incidence of overcrowded in the ED of Adi Husada Kapasari Hospital (p-value 0.898 and r=0.038). Conclusion: For non-large-scale emergency departments like the ED of Adi Husada Kapasari Hospital, the implementation of triage is not significantly related to the overcrowded incidence, although some studies and theories state otherwise, that the accuracy of emergency room nurses in triaging can help reduce patients overcrowding and treat patients immediately. Further research could explore this gap through a larger sample or by involving or comparing more populations of various type of EDs.